Radiative gravitational collapse to black holes in five dimensions - Mena, Filipe C. (2012)
We review recent results about the modelling of radiating gravitational collapse to Schwarzschild-Tangherlini black holes. In particular, we prove that classes of five dimensional collapsing solutions built on Riemannian Bianchi IX spatial metrics can be matched to radiating exteriors given by the Bizo´n-Chmaj-Schmidt metric. We show that the data at the boundary for the exterior can be chosen to be close to the data for the Schwarzschild-Tangherlini solution which is known to be stable